2022
DOI: 10.1016/j.jep.2022.115064
|View full text |Cite
|
Sign up to set email alerts
|

Mild moxibustion for Irritable Bowel Syndrome with Diarrhea (IBS-D): A randomized controlled trial

Abstract: To evaluate the effects of mild moxibustion (MM) for the treatment of irritable bowel syndrome with diarrhea (IBS-D) through comparisons with those of placebo moxibustion. Patients and Methods:This was a single-site, randomized controlled trial was conducted at Shanghai Research Institute of Acupuncture and Meridian in China and enrolled 76 participants who met the Rome IV diagnostic criteria for IBS-D between May 2017 and December 2019. 76 participants were randomized to either mild moxibustion (MM) or placeb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…These trials included the clinical observation of 3,400 patients, resulting in multiple evidence-based data supporting the clinical effectiveness of moxibustion. High-quality clinical evidence has been obtained for warm moxibustion in the treatment of diarrheal irritable bowel syndrome [4] and for moxibustion combined with acupuncture in the treatment of Crohn disease [5] .…”
Section: Clinical Application Of Moxibustionmentioning
confidence: 99%
“…These trials included the clinical observation of 3,400 patients, resulting in multiple evidence-based data supporting the clinical effectiveness of moxibustion. High-quality clinical evidence has been obtained for warm moxibustion in the treatment of diarrheal irritable bowel syndrome [4] and for moxibustion combined with acupuncture in the treatment of Crohn disease [5] .…”
Section: Clinical Application Of Moxibustionmentioning
confidence: 99%
“…Modern research has confrmed that moxibustion creates far and nearinfrared radiation and heat and light radiation. Far infrared radiation penetrates the internal organs and meridians and acts directly on the focal area, which can penetrate into the circulation and nervous system and be absorbed by living tissues to achieve therapeutic efects [32], so moxibustion is widely used in the treatment of various diseases [33][34][35]. According to the theory of Chinese medicine, moxibustion therapy is applied to certain acupuncture points of the human body through moxa wool or other ignited drugs so that its heat and medicinal efects can penetrate the skin to warm the meridians, dispel cold and dampness, and unblock the meridians to regulate the body's qi and blood [36].…”
Section: Mechanism Of Moxibustionmentioning
confidence: 99%
“…[9] ACU has a long history and rich experience in the treatment of gastrointestinal diseases. In addition, a large number of clinical studies have proved that ACU is safe and effective in the treatment of IBS, [10,11] and evidence-based studies have also confirmed this view. [12,13] ACU and moxibustion therapy can improve qi and blood function, enhance immunity and improve mental health by stimulating specific acupoints in the human body.…”
Section: Introductionmentioning
confidence: 99%